Impact of foreign direct investment on economic growth in Nigeria: Mediating role of institutional quality - Illo, Faruk Muhammad; Oladipo, Olajide; Azu, Nnanna P. (Edelweiss Applied Science and Technology, 2025)
This study is motivated by the persistent disconnection between rising Foreign Direct Investment (FDI) inflows and Nigeria’s economic development, with a focus on understanding the mediating role of institutional quality. The primary aim is to investigate how political rights and civil liberties influence the relationship between FDI and economic growth in Nigeria. Covering the period from 1981 to 2022, the study adopts the Autoregressive Distributed Lag (ARDL) model to assess both short- and long-run dynamics using annual time series data. Key variables include GDP per capita, FDI inflows, political rights, civil liberties, labor force participation, and financial development. The findings reveal that FDI negatively affects economic growth by up to 56.4% in the short run and 30.6% in the long run. However, political rights positively moderate the impact of FDI, improving growth outcomes by approximately 123% in the long run. Conversely, civil liberties exhibit a negative moderating effect in both time horizons. The results underscore that without institutional reform, FDI may not deliver its expected economic benefits. The study recommends that Nigeria strengthen its institutional frameworks—particularly political rights—enhance transparency, and develop absorptive capacity to fully harness FDI’s growth potential and foster inclusive, long-term economic development.